(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Triphla is a great formulation described in Ayurveda texts by our ancient sages in past. It has a lot of uses for body wellness. It contains Embelica officinalis (Amla ), Terminalia chebula (Haritaki ) & Terminalia bellirica (Bahera) in equal quantities . It can be used as internal and external application for body as very fine powder and coarse powder as per the requirement of the Ayurvedic procedures. It is content of various Ayurvedic formulations. It helps to improve our digestive fire. If digestive fire of body is normal then all the Dhatavagnies will function normally which leads to proper production of all the Doshas, Dhatu & Mala of our body for a healthy life. In case of Eye diseases Majja Dhatu formation is disturbed which the result of disturbed metabolism. While kostha aids in the proper excretion of waste materials, Jatharagni aids in the proper digestion and assimilation of consumed food as well as the proper operation of other types of Pitta-metabolic factors, particularly Alochaka pitta (rods and cones functional entity) in the eyes. The longevity, health, and diseasefree life are maintained by the proper operation of these two systems Several combinations of medications that work on both the aforementioned systems were explained by ancient Ayurveda experts. In this article we will discuss about only ocular health in case of Triphla.